Between the plough and the pick informal, artisanal and small-scale mining in the contemporary world - Lahiri-Dutt, Kuntala 1956-; Australian National University Press (Acton, A.C.T. ANU Press, 2018)
Between the Plough and the Pick deepens our understanding of informal, artisanal and small scale mining, popularly known as ASM. The book engages with wider scholarly conceptualisations of contemporary global social, agrarian and political changes, whilst underlining the roles that local social political historical contexts play in shaping mineral extractive processes and practices. It shows that the people who are engaged in these mining practices are often the poorest and most exploited labourers erstwhile peasants caught in the vortex of global change, who perform the most insecure and dangerous tasks. Although these people are located at the margins of mainstream economic life, they collectively produce enormous amounts of diverse material commodities and find a livelihood (and often a pathway out of oppressive poverty). The contributions to this book bring these people to the forefront of debates on resource politics. The contributors are international scholars and practitioners who explore the complexities in the histories, in labour and production practices, the forces driving such mining, the creative agency and capacities of these miners, as well as the human and environmental costs of ASM. They show how these informal, artisanal and small scale miners are inextricably engaged with, or bound to, global commodity values, are intimately involved in the production of new extractive territories and rural economies, and how their labour reshapes agrarian communities and landscapes of resource access and control. This book drives home the understanding that, collectively, this social and economic milieu redefines our conceptualisation of resource politics, mineral dependent livelihoods, extractive geographies of resources and commodities, and their multiple meanings.
Reframing the debate on informal mining / Kuntala Lahiri-Dutt -- Section One: Historical antecedents and value making. Artisanal gold rush mining and frontier democracy: Juxtaposing experiences in America, Australia, Africa and Asia / Deborah Fahy Bryceson -- Tanzanite: Commodity fiction or commodity nightmare? / Katherine C. Donahue -- Agrarian distress and gemstone mining in India: The political economy of survival / Arnab Roy Chowdhury and Kuntala Lahiri-Dutt -- The social ecology of artisanal mining: Between romanticisation and anathema / Saleem H. Ali -- Section Two: Precarious and gendered labour. Theorising transit labour in informal mineral extraction processes / Ranabir Samaddar -- A good business or a risky business: Health, safety and quality of life for women small scale miners in PNG / Danielle Lynas -- Rice, sapphires and cattle: Work lives of women artisanal and small scale miners in Madagascar / Lynda Lawson -- Is it possible to integrate health and safety risk management into mechanised gold processing? A methodology for artisanal and small scale mining communities in the Philippines / Gernelyn Logrosa, Maureen Hassall, David Cliff and Carmel Bofinger -- Resources and resourcefulness: Gender, human rights and resilience in artisanal mining towns of eastern Congo / Rachel Perks, Jocelyn Kelly, Stacie Constantian and Phuong Pham -- Section Three: Conflicts and governance. Historical trajectory of gold mining in the Nilgiri Wayanad region of India / Amalendu Jyotishi, Kuntala Lahiri-Dutt and Sashi Sivramkrishna -- Conflicts in marginal locations: Small scale gold-mining in the Amazon / Marjo de Theije and Ton Salman -- Small-scale gold-mining: Opportunities and risks in post-conflict Colombia / Alexandra Ur?an -- Muddy rivers and toxic flows: Risks and impacts of artisanal gold mining in the riverine catchments of Bombana, Southeast Sulawesi (Indonesia) / Sara Beavis and Andrew McWilliam -- Artisanal and small-scale mining governance: The emerging issue of unregulated mining in Lao PDR / Daniele Moretti and Nicholas Garrett -- Reassembling informal gold-mining for development and sustainability? Opportunities and limits to formalisation in India, Indonesia and Laos / Keith Barney.
Includes bibliographical references.
Keywords: Mineral industries -- Developing countries; Mines and mineral resources -- Developing countries